2018
DOI: 10.1021/acs.chemrestox.7b00299
|View full text |Cite
|
Sign up to set email alerts
|

Development of Polyclonal Antibodies for Detection of Diosbulbin B-Derived cis-Enedial Protein Adducts

Abstract: Diosbulbin B (DSB), a major component of herbal medicine Dioscorea bulbifera L. (DB), can be metabolized to an electrophilic intermediate, DSB-derived cis-enedial (DDE). DDE was suggested to contribute to the hepatotoxicity observed in experimental animals and humans after their exposure to DSB. Our previous work found that DDE reacted with primary amino and/or sulfhydryl groups of hepatic protein. The objective of the study was to develop polyclonal antibodies that can recognize DDE-derived protein adducts. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Facilitating the recognition of the DDE-derived protein adduction, we further successfully raised the polyclonal antibodies with high titers in rabbits immunized with the antigen prepared by reaction of KLH with DDE. Immunoblot analysis of the liver homogenates obtained from mice given different doses of DSB showed that much more intense protein bands were observed in the samples from 200 mg/kg DSB-treated mice than that from mice administered with 150 mg/kg DSB, similar to the dose-13 dependent hepatotoxicity observed above (Hu et al, 2018).…”
Section: Diosbulbin Bsupporting
confidence: 64%
“…Facilitating the recognition of the DDE-derived protein adduction, we further successfully raised the polyclonal antibodies with high titers in rabbits immunized with the antigen prepared by reaction of KLH with DDE. Immunoblot analysis of the liver homogenates obtained from mice given different doses of DSB showed that much more intense protein bands were observed in the samples from 200 mg/kg DSB-treated mice than that from mice administered with 150 mg/kg DSB, similar to the dose-13 dependent hepatotoxicity observed above (Hu et al, 2018).…”
Section: Diosbulbin Bsupporting
confidence: 64%
“…DSB, the major component in traditional Chinese medicine DBL, was found to be hepatotoxic in our early studies, and its cis -enedial metabolite was responsible for the reported toxicity. , The reactive intermediate was found to react with GSH, protein, and DNA. ,, The present study aimed at the interaction of intermediate 2 (Scheme ) with polyamines/biogenic amines/amino acids, along with its potential correlation with DSB-induced cell death. We employed BBM to trap toxic cis -enedial intermediate 2 resulting from the bioactivation of the furan-ring moiety of DSB.…”
Section: Discussionmentioning
confidence: 97%
“…The regression curves of the competitors were fitted Western Blot. Protein (1.0 μg/well) obtained from in vitro and in vivo studies were separated by SDS-PAGE as we previously described, 32 and then the proteins resolved were transferred to polyvinylidene fluoride (PVDF) membranes by the semidry technique at 10 V for 15 min. After transferring, the PVDF membranes with protein bands were blocked with 5% nonfat milk in TBST buffer (0.05% Tween 20, 0.15 M NaCl, and 10 mM Tris at pH 7.5) for 2 h at room temperature.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%